Unfriendly to liberty : loyalist networks and the coming of the American Revolution in New York City - Minty, Christopher F., 1988- (Cornell University Press, 2023)
"This book examines political mobilization and the origins of loyalism in Manhattan in the decade or so prior to the American Revolution. It focuses on the emergence of the DeLancey faction in New York City politics, arguing that prerevolutionary partisanship and associationism influenced New Yorkers' allegiances during the American Revolution"--